2004
DOI: 10.1002/mde.1202
|View full text |Cite
|
Sign up to set email alerts
|

Vertical group formation: A social process perspective

Abstract: Vertical groups are a common occurrence that is rarely studied as a group-level phenomenon. This paper brings attention to the vertical group, as a collective actor, and group formation processes. We define the vertical group and describe, in brief, why they exist. We explore the issue of how they form and the social processes under which different types of groups are likely to emerge. These include trial and error learning, social learning, and social identification. We introduce a framework that shows how va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…Nishiguchi, 1994;Lane, 1996). In terms of the framework recently developed by Peteraf and Shanley (1997) and Shanley and Peteraf (2004), each industry in each country may be endowed with different, and possibly inconsistent 'vertical groups', through country-specific social generative processes. In terms of the framework developed by Jacobides et al (2006), each country may have a different, distinct ''industry architecture'', i.e.…”
Section: What Determines Success In Global Expansion? Background and mentioning
confidence: 99%
See 2 more Smart Citations
“…Nishiguchi, 1994;Lane, 1996). In terms of the framework recently developed by Peteraf and Shanley (1997) and Shanley and Peteraf (2004), each industry in each country may be endowed with different, and possibly inconsistent 'vertical groups', through country-specific social generative processes. In terms of the framework developed by Jacobides et al (2006), each country may have a different, distinct ''industry architecture'', i.e.…”
Section: What Determines Success In Global Expansion? Background and mentioning
confidence: 99%
“…Thus, each country has a distinct evolutionary trajectory in each industry where capabilities, scope, and the institutional context interact and shape the nature of the participants, leading to the creation of fairly distinct 'vertical groups' (Shanley and Peteraf, 2004) along the way. It is exactly these inter-national differences in the nature of these 'vertical groups' in otherwise identical industries that hamper the exportability of competitive advantage.…”
Section: The Division Of Labor Across Vertical Boundaries: Path-depenmentioning
confidence: 99%
See 1 more Smart Citation
“…McNamara et al, 2003); the existence of communities of practice (Brown and Duguid, 1991) has been argued to contribute to the emergence of identity}central to the psychological approach to constructing strategic groups}(e.g. Peteraf and Shanley, 1997;Reger and Huff, 1993); and the influence of networks of relationships (Granovetter, 1985) has been shown to influence choices across strategic groups (Garcia-Pont and Nohria, 2002), as well as the formation of 'vertical groups' (Shanley and Peteraf, 2004). The validity of the analogy between strategic groups research and NIE at this level can be found in the fact that strategic groups and NIE researchers investigating factors at this level refer to widely overlapping source references.…”
Section: Nie and Strategic Groups Analysismentioning
confidence: 99%
“…Nath and Gruca, 1997). Thomas and Carroll (1994) explored the interplay between strategic groups studies focusing on network relationships, cognitive structures and asset endowment and positioning, and Peteraf and Shanley (1997) and Shanley and Peteraf (2004) analyzed how economic, historical and institutional factors influence the processes of strategic group emergence and structuration. The present framework provides a theoretical backbone to such analyses and completes our perspective in the sense that all studies can be mapped to one of the four levels of analysis.…”
Section: Implications Of the Analogy With Nie For Strategic Groups Rementioning
confidence: 99%